In vitro Evaluation of Repair Bond Strength to Bulk-fill Composites Using Two Silane-Free Universal Adhesives, with and without Silane Application - Alara AKSOY; Nazmiye DÖNMEZ (Bezmiâlem Science)
Objective: To evaluate the effect of silane-free universal adhesives systems on the repair shear bond strength (SBS) of sonic-activated bulk-fill [SonicFill (SF) Kerr, USA] composite applying additional silane in the repair of bulk-fill composite. Methods: Sonic-activated bulk-fill composite samples (n=40) were prepared using a teflon mold (6 mm x 4 mm) and polymerized. Then all samples were kept in an incubator to simulate the aging process at 37 °C for one month. Aged composite samples were embedded in acrylic resin. For the repair, the specimen surfaces were roughened with a diamond bur. They were divided into 2 groups (n=20) according to the adhesive system used and then into two subgroups (n=10) as additional silane was applied or unapplied. Adhesive systems Ambar Universal Bond (AUB), (FGM, Brazil), G-Premio Bond (GPB) (GC, USA) and silane (G-Multi primer GC, Tokyo, Japan) were applied according to the manufacturer’s instructions. Samples were subjected to a shear bond test in a universal testing device. For statistical analysis, one-way ANOVA test was performed (p<0.05). Results: The highest SBS value was obtained in the silane-treated AUB group (21.88±6.4), while the lowest SBS value was obtained in the silane-treated GPB group (16.07±6.2). No statistically significant difference was observed between all groups (p<0.05). Conclusion: Additional silane application does not affect the SBS of universal adhesives on an SF composite material.